Solid Contents of Stacked Wood (Eucalyptus hybrid) for Pulp and Paper Industry - Sharma, R. P.; Jain, R. C. (Indian Forester, 1976)
Eucalyptus hybrid is mainly supplied to the Pulp and Paper Industry. To know its solid volume correspondiug to stacked volume, measured in the field, tables have been prepared. Data of Bijnor Plantation Division has been used. The regression equation of type V= a+b S where V=solid volume, S= stacked volume and a and b are Constants, was found to fit the data and was utilized.